EWSR1/ELF5 induces acute myeloid leukemia by inhibiting p53/p21 pathway. Issue 12 (25th November 2016) - Endo, Akifumi; Tomizawa, Daisuke; Aoki, Yuki; Morio, Tomohiro; Mizutani, Shuki; Takagi, Masatoshi
Abstract : The Ewing sarcoma breakpoint region 1 ( EWSR1 ) gene is known to fuse with various partner genes to promote the development of the Ewing sarcoma family of tumors and other sarcomas. In contrast, the association of EWSR1 chimeric fusion genes with leukemia has rarely been reported. We identified a novel EWSR1 ‐associated chimeric fusion gene in a patient with acute myeloid leukemia harboring 46, XY, t (11; 22) (p13; q12) karyotype abnormality. The patient was refractory to intensified chemotherapy including hematopoietic stem cell transplantation. Total RNA paired‐end sequencing identified a novel chimeric fusion gene as EWSR1/ELF5, a member of the E26 transformation‐specific transcription factor family. Transduction of EWSR1/ELF5 to NIH3T3 cells induced transformation by attenuating with the p53/p21‐dependent pathway. The injection of EWSR1/ELF5‐ transduced NIH3T3 cells into NSG‐SCID mice systematically induced the development of tumors in vivo . These results revealed the oncogenic potency of EWSR1/ELF5 . Abstract : Novel chimeric fusion gene, EWSR1/ELF5, was identified in a patient with acute myeloid leukemia (AML). EWSR1/ELF5 induced cetllular transformation by attenuating with the p53/p21‐dependent pathway.